Six new species of the gutless genus Olavius (Annelida: Clitellata: Tubificidae) from New Caledonia - Erséus, Christer; Bergfeldt, Ulrika (Zootaxa, 2007)
Six species of the gutless marine tubificid genus Olavius Erséus, 1984 (Phallodrilinae), O. paraloisae sp. nov., O. amplectens sp. nov., O. isomerus sp. nov., O. fidelis sp. nov., O.lifouensis sp. nov., and O. nivalis sp. nov., are described from shallow-water sediments in New Caledonia (including the Loyalty Islands), in the South West Pacific Ocean. Olavius amplectus is similar (but not necessarily closely related) to a North West Atlantic species. The others appear closely related to previously described taxa in the Indo-West Pacific region, but they differ in the number of secondary body annuli, the number, shape and arrangement of chaetae, or in details of the male genitalia and/or spermathecae. Moreover, fixed (contracted) specimens of O. nivalis measured up to 34 mm length, which makes it one of the largest species of gutless Phallodrilinae known to date.